Decision-making preferences and risk factors regarding early adolescent pregnancy in Ghana: stakeholders' and adolescents' perspectives from a vignette-based qualitative study - Luchuo Engelbert Bain; Seda Muftugil-Yalcin; Mary Amoakoh-Coleman; Marjolein B. M. Zweekhorst; Renaud Becquet; Tjard de Cock Buning (BMC, 2020)
Abstract Background Worldwide, over half of the adolescent pregnancies recorded are unintended. The decision to continue the pregnancy to term or to opt for an abortion is a constant dilemma that is directly or indirectly influenced by stakeholders and also by the wider social environment. This study aimed at understanding the perceived decision-making preferences and determinants of early adolescent pregnancy in the Jamestown area of Accra in Ghana. Methods A vignette-based qualitative study design was used. Eight focus group discussions were carried among various purposively selected groups of participants: parents, teachers, adolescent students who had not been pregnant before, and adolescents who had had at least one pregnancy in the past. The vignette was a hypothetical case of a 15-year-old high school student who had not experienced her menses for the past 6 weeks. The data were analyzed using a thematic analysis approach. Results Lack of parent-daughter communication, the taboo on discussing sex-related issues in households and weak financial autonomy were considered to be the main contributing factors to the high early adolescent pregnancy rates in the community. Partner readiness to assume responsibility for the girl and the baby was a key consideration in either continuing the pregnancy to term or opting for an abortion. The father was overwhelmingly considered to be the one to take the final decision regarding the pregnancy outcome. Irrespective of the fact that the respondents were very religious, opting for an abortion was considered acceptable under special circumstances, especially if the pregnant adolescent was doing well in school. Conclusion Inadequate and inappropriate communication practices around sexuality issues, as well as weak financial autonomy are the major predictors of early adolescent pregnancy in this community. The father is perceived to be the main decision maker regarding a young adolescent's pregnancy outcome. Policy-makers should carefully evaluate the implications of this overwhelming perceived desire for the father to be the final decision-maker regarding adolescent pregnancy outcomes in this community.